Pengaruh Ukuran Perusahaan dan Leverage terhadap Profitabilitas pada Perusahaan BUMN di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Umami, Ilham Rois; Nurhasanah, Nunung; Nadeak, Banuara (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the effect of company size and leverage on profitability in state-owned companies on the Indonesia Stock Exchange for the 2019-2023 period. The research method used is a quantitative research method. The research results show that simultaneously and partially company size and leverage have a significant effect on the profitability of state-owned companies on the Indonesia Stock Exchange for the 2019-2023 period.